The Effectiveness of Audio-Visual Health Education Media on Diet on The Level of Knowledge and Attitude of Adolescent in the Prevention of Type 2 Diabetes Mellitus - Mansyah, Barto; Rahmawati, Fetty (Media Keperawatan Indonesia, 2021)
Efforts to increase knowledge and attitudes in adolescents require a learning media that can not only be used in the world of education but also in the health sector, especially in the prevention of DM where one of the risk factors for DM is an unhealthy diet. One of the media that can be used is audio visual. This study aims to analyze the effect of audio-visual media on diet on the level of knowledge and attitudes of adolescents in preventing type 2 diabetes. This type of research is a quasi-experimental study with a pretest-posttest with control group design. The results showed that there were significant differences in the mean value of knowledge (p value 0,039 <0,005) and attitude score (p value 0,001 <0,005) which were significant between the intervention group and the control group. The mean increase in the knowledge value of the intervention group was 16,27 higher than the control group was 9,20. In the attitude variable, the mean score of attitudes in the intervention group was 13,27 higher than the mean value in the control group, namely 9,20, so it can be concluded that the intervention group in the form of audio-visual health education showed better results in increasing knowledge and attitudes about diet in the prevention of type 2 diabetes.